Event-Related Potential Correlates of Valence, Arousal, and Subjective Significance in Processing of an Emotional Stroop Task - Imbir, Kamil K.; Duda-Goławska, Joanna; Pastwa, Maciej; Jankowska, Marta; Żygierewicz, Jarosław (Frontiers in Human Neuroscience, 2021)
The present study is the first to measure event-related potentials associated with the processing of the emotional Stroop task (EST) with the use of an orthogonal factorial manipulation for emotional valence, arousal, and subjective significance (the importance of the current experience for goals and plans for the future). The current study aimed to investigate concurrently the role of the three dimensions describing the emotion-laden words for interference control measured in the classical version of the EST paradigm. The results showed that reaction times were affected by the emotional valence of presented words and the interactive effect of valence and arousal. The expected emotional arousal effect was only found in behavioral results for neutrally valenced words. Electrophysiological results showed valence and subjective significance correlated with the amplitude differences in the P2 component. Moreover, the amplitude of the N450 component varied with the level of subjective significance. This study also demonstrated that exploratory event-related potential analysis provides additional information beyond the classical component-based analysis. The obtained results show that cognitive control effects in the EST may be altered by manipulation in the subjective significance dimension.